Ustanovitev Mednarodne organizacije dela leta 1919 - Kresal, Barbara (Socialno delo, 2019)
The contribution analyses the establishment of the International Labour Organisation in 1919, after the end of the First World War, which formed part of the Versailles Peace Treaty, and the development of this international organisation during its 100 years of existence. The role of labour rights and its regulation at the international level as well as the role of the International Labour Organisation in this respect is discussed. The development of the regulation of working time in the light of the relevant ILO conventions is taken as an example. The contribution compares the situation in the world of work as it was 100 years ago and as it is today. Social justice and decent work are still the declared, but not achieved goals of the International Labour Organisation.
Keywords: delovni čas; delovno pravo; dostojno delo; International Labour Organisation; socialna pravičnost